Effects of dietary Vitamin E level and source on sow, milk, and piglet concentrations of α-tocopherol - Shelton, N.W.; Yang, H.; Mahan, D.C.; Nelssen, Jim L.; Tokach, Michael D.; Goodband, Robert D.; DeRouchey, Joel M.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
A total of 126 gilts and sows (PIC 1050) and their litters were used to determine the effect of dietary vitamin E level and source on sow plasma, milk, and piglet tissue concentrations of α-tocopherol. The 6 dietary treatments included 2 levels of dl-α- tocopherol acetate (Syn E) at 44 and 66 mg/kg (40,000 and 60,000 mg/ton) and 4 levels of d-α-tocopherol acetate (Nat E) at 11, 22, 33, and 44 mg/kg (10,000, 20,000, 30,000 and 40,000 mg/ton). From breeding through d 69 of gestation, sows were fed 4.5 lb/d of a diet containing 40% dried distillers grains with solubles (DDGS), 0.30 ppm added Se, and no added vitamin E. Vitamin E treatments were fed from d 70 of gestation through weaning (d 21). Plasma was collected from sows on d 69 and 100 of gestation, at farrowing, and at weaning. Colostrum (d 1) and milk samples (weaning) were also collected. Plasma from 3 pigs per litter and heart and liver samples from 1 pig per litter were collected at weaning. All plasma, milk, and tissue samples from 6 sows and litters per treatment were analyzed for α-tocopherol.
Keywords: Swine; α-tocopherol; Bioavailability; Natural vitamin E; Sow